Teknik Wortliste dalam Meningkatkan Kemampuan Membaca Bahasa Jerman - Muhammad Yusran; Laelah Azizah; Syukur Saud (Academic : Journal of Social and Educational Studies, 2023)
Abstract. This research is a Quasi-Experimental research with the form of Pretest-Posttest Only Control Group Design which aims to find out data and information about the effectiveness of using the Wortliste technique in improving German reading skills of class XI MIPA MAN 1 Kota Makassar. The population of this study were all students of class XI MIPA MAN 1 Makassar City, totaling 178 students, then the samples in this study were students of class XI MIPA 4 as an experimental class totaling 28 students, and class XI MIPA 1 as a control class totaling 28 students. selected at random (random sampling). Data analysis techniques using t-test. Based on the results of the research data, it shows that the value of ????ℎ???????????????????? = 2.938 > ttable = 2.005 with a significant level of 0.05. The results showed that the use of the Wortliste technique was effective in improving the German reading skills of class XI MIPA MAN 1 Kota Makassar.Keywords: Effektivnesss, Wortliste, Reading, German